2019
DOI: 10.3208/jgssp.v07.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydromechanical properties of plant roots in unsaturated soil shear strength

Abstract: Plants increase slope stability through mechanical reinforcement by roots and transpiration-induced matric suction (hence increase in soil shear strength; known as hydrological reinforcement). The effects of root water status on root biomechanical properties (e.g. volume change and tensile properties), and eventually the shear strength of rooted soil, have not yet been fully investigated. This paper studies the hydromechanical properties of plant roots and estimates how these properties may affect unsaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Plant roots permeated to the soil matrix form a soil-root composite and resist shearing by mobilising the roots' tensile or/and flexural properties and the soil-root interface friction (Gray and Barker 2004;Schwarz et al 2010). In addition to mechanical reinforcement, recent research has demonstrated that the removal of soil moisture through the process of plant transpiration and root-water uptake induces soil matric suction, which in turn increases the soil shear strength (Leung et al 2017(Leung et al , 2019Boldrin et al 2018Boldrin et al , 2020Switala et al 2018;Mahannopkul and Jotisankasa 2019;Ni et al 2019;Yildiz et al 2019) To reveal and understand the root reinforcement mechanisms, it is vital to identify the stress paths relevant to slope failure. Figure 1 shows a marginally stable vegetated slope and three major stress states in which their major principal stresses are rotating along a slip surface from the slope crest to toe.…”
Section: Introductionmentioning
confidence: 99%
“…Plant roots permeated to the soil matrix form a soil-root composite and resist shearing by mobilising the roots' tensile or/and flexural properties and the soil-root interface friction (Gray and Barker 2004;Schwarz et al 2010). In addition to mechanical reinforcement, recent research has demonstrated that the removal of soil moisture through the process of plant transpiration and root-water uptake induces soil matric suction, which in turn increases the soil shear strength (Leung et al 2017(Leung et al , 2019Boldrin et al 2018Boldrin et al , 2020Switala et al 2018;Mahannopkul and Jotisankasa 2019;Ni et al 2019;Yildiz et al 2019) To reveal and understand the root reinforcement mechanisms, it is vital to identify the stress paths relevant to slope failure. Figure 1 shows a marginally stable vegetated slope and three major stress states in which their major principal stresses are rotating along a slip surface from the slope crest to toe.…”
Section: Introductionmentioning
confidence: 99%
“…e results showed that the shear strength of a root-soil complex with significant lateral roots and vertical roots increased more than that of a root-soil complex with only lateral roots. Leung et al [31] conducted experiments on six trees of a similar age under light and no-light conditions and found that root water absorption had a relatively small contribution to plant soil-induced suction, and root water absorption had a relatively small impact on the soil water retention curve. Veylon et al [32] used the direct shear box test method to study three tree species of reforestation on slopes in Yunnan and quantified the influence of soil water content on soil reinforced by plant roots.…”
Section: Introductionmentioning
confidence: 99%